Ovarian morphology is associated with insulin resistance in women with polycystic ovary syndrome: a cross sectional study - Reid, Sara Pittenger (Fertil Res Pract, 2017)
BACKGROUND: Polycystic ovary syndrome (PCOS) is a very common disorder well known to be associated with insulin resistance and metabolic disease. Insulin resistance is likely involved in the promotion of the PCOS reproductive phenotype and may mediate some of the ovarian morphology seen in the disorder. The phenotype of each individual woman with PCOS can vary widely as can her metabolic risk. METHODS: This is a cross-sectional study of patients seen in a multidisciplinary PCOS clinic at the University of California at San Francisco between 2006 and 2014. All participants underwent systematic evaluation with anthropometric measurements, comprehensive skin exam, transvaginal ultrasound and laboratory studies at the time of their initial visit to the clinic. Serum samples were stored and androgen studies were carried out on all stored samples at the University of Virginia. Logistic regression was employed to evaluate the association between ovarian volume or follicle number and metabolic parameters (fasting insulin, HOMA-IR, fasting glucose, 2 h glucose, waist circumference) and hyperandrogenism (free testosterone, total testosterone, DHEAS, acanthosis nigricans), controlling for age. RESULTS: Three-hundred thirteen patients seen during the study period met Rotterdam criteria for PCOS and had sufficient measurements for inclusion in our analysis. The odds ratio of elevated HOMA-IR for patients with a maximum ovarian volume >10 cc was 1.9 compared to those with a maximum ovarian volume of ≤10 cc (95% CI 1.0–3.4). The odds ratio of abnormal fasting insulin for patients with higher ovarian volume was 1.8 (95% CI 1.0–3.4) compared with those with lower ovarian volume. Follicle number was not significantly associated with any metabolic parameters. CONCLUSIONS: Increased ovarian volume is associated with markers of insulin resistance in PCOS. In concordance with prior studies, we did not find follicle number to be predictive of metabolic risk. Ovarian volume may serve as a useful tool to aid clinicians in their risk stratification and counseling of patients with PCOS.